Is Susila Budhi Dharma (Subud) a Religion? - Watini Watini (Graduate Program of Pontianak Institute of Islamic Studies, 2017)
The government of Indonesia has recognized six offical religions based on certain categories by law. Susila Budhi Dharma known as SUBUD is not included as one of them. The debate on the inclusion of SUBUD as a religion has existed since its existance. This work attemps to explore the experience of SUBUD in dealing with the acknowledment both by people and the schoolars in religious studies and the discource on it. Richard King believes that Subud is a religion since there is mysticim in it (submission to God) with latihan kejiwaan. He may say that it is constructed like what laso is prascticed in Christianity. Subud is not a religious teaching claimed by Subud’s members but Subud is as a religion since the latihan kejiwaan is from God and appropriate with God’s will. In the discussion of Marxian, Durkheimian and Freudian, Subud is considered as a religion since it tends to promote dependance and can disturb economy. While in the views of both Weberian and Eliadean, SUBUD is considered as a religion because it is related to sacred intities and is traditonalism. The works suggests that deeper information would be beneficial for the people within religious studies to accommodate Subud as a religion based on theories in the field. Talal Asad’s theory can develop Subud terminology that it is as a religion since it is categorized as an organization that have structures of leaders and people. Indeed, Subud has proven to separate from the states for its growing and developtment in European countries and the USA.